2019
DOI: 10.3389/fphar.2019.00682
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Atypical Dopamine Uptake Inhibitor (S)-CE-123 Partially Reverses the Effort-Related Effects of the Dopamine Depleting Agent Tetrabenazine and Increases Progressive Ratio Responding

Abstract: Animal studies of effort-based choice behavior are being used to model effort-related motivational dysfunctions in humans. With these procedures, animals are offered a choice between high-effort instrumental actions leading to highly valued reinforcers vs. low effort/low reward options. Several previous studies have shown that dopamine (DA) uptake inhibitors, including GBR12909, lisdexamfetamine, methylphenidate, and PRX-14040, can reverse the effort-related effects of the vesicular monoamine transport blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 74 publications
6
42
0
1
Order By: Relevance
“…In contrast, at 10 mg/kg a downward trend of dopamine levels was observed from 80 to 180 min following administration. This lack of stimulation of dopamine transmission in the NAc shell is consistent with what observed at the dose of 24 mg/kg ip [25], although a recent study reported that (S)-CE-123 at doses of 10 and 100 mg/kg increased dopamine extracellular levels in the NAc shell of mice [26]. Differences in the utilized doses of (S)-CE-123 in the metabolic pathway of species (mice vs. rats), together with the specificity of the brain area implanted, might be the reason of the lack of increase observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, at 10 mg/kg a downward trend of dopamine levels was observed from 80 to 180 min following administration. This lack of stimulation of dopamine transmission in the NAc shell is consistent with what observed at the dose of 24 mg/kg ip [25], although a recent study reported that (S)-CE-123 at doses of 10 and 100 mg/kg increased dopamine extracellular levels in the NAc shell of mice [26]. Differences in the utilized doses of (S)-CE-123 in the metabolic pathway of species (mice vs. rats), together with the specificity of the brain area implanted, might be the reason of the lack of increase observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…TBZ also reduced climbing in the FST, indicating that TBZ generally reduces highly active behaviors. Numerous studies have reported that TBZ and DA antagonists affect effortful behaviors in rodents when animals have to work (lever pressing or climbing a barrier) in order to obtain a high-value reinforcer when they concurrently have a free low-value reinforcer (Pardo et al, , 2015Nunes et al, 2013;Randall et al, 2014;Yohn et al, 2015aYohn et al, ,b, 2016aContreras-Mora et al, 2018;Correa et al, 2018;Rotolo et al, 2019;Yang et al, 2020). In conclusion, the three-choice T-maze task can evaluate preference for exercise and anergia induced by DA impaired function, and this task could have potential clinical relevance for modeling the psychomotor retardation, anergia, fatigue, and the low-effort bias seen in some human psychopathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse tasks have been used in rodents for evaluating behavioral activation and effort-related decision making, including tasks that give animals the option of vigorously working (lever pressing or climbing a barrier) to obtain access to more highly valued reinforcers vs. approaching and consuming a less preferred reinforcer (Cousins et al, 1994;Salamone and Correa, 2002;Salamone et al, 2016;Mott et al, 2009;Mai et al, 2012;Pardo et al, 2012Pardo et al, , 2015Randall et al, 2012;Sommer et al, 2014;Yohn et al, 2015aYohn et al, , 2016bCorrea et al, 2018;SanMiguel et al, 2019). In these tasks, conditions that alter DA transmission, such as administration of DA antagonists or tetrabenazine (TBZ), can alter behavioral activation and reduce selection of high-effort choices in rats (Nunes et al, 2013;Randall et al, 2014;Hosking et al, 2015;Pardo et al, 2015;Yohn et al, 2015aYohn et al, , 2016aContreras-Mora et al, 2018;Rotolo et al, 2019). TBZ acts by inhibiting the vesicular monoamine transporter-type 2 (VMAT-2), which leads to a blockade of vesicular storage and a depletion of monoamines, with its greatest effects at low doses being on striatal DA in rats and mice (Pettibone et al, 1984;Nunes et al, 2013;López-Cruz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A progressive ratio version of the EfRT, due to the higher ratio trials also requiring more time, may produce results more similar to the ones shown by Floresco et al ( 2008 ) but this was not tested here. When the reward schedule is not fixed but instead a progressive ratio of the task is used, dopaminergic drugs such as lisdexamfetamine (Yohn et al 2016c ), PRX-14040 (Yohn et al 2016b ), and CE-123 (Rotolo et al 2019 ) appear to potentiate high effort responding. It is possible the progressive ratio schedule results in reduced levels of effortful behaviour when chow is also present, as indicated by the relatively low numbers of lever presses, thus providing a better baseline for the assessment of whether drugs increase motivation.…”
Section: Discussionmentioning
confidence: 99%